Foreign direct investments concepts, methodologies, tools, and applications (IGI Global, Business Science Reference, 2020)
"This book explores the importance of global stocks to economic structures and explores the effects that these holdings have on the financial status of nations. It also provides a systems approach to investment projects in a globalized and open society"--